Varying oropharyngeal colostrum administration dosages on outcomes associated with very low birth weight infants: a randomised controlled trial protocol - Juan Chen; Zhenyan Fu; Yao Jin; Chi Huang; Ji Jin; Yingping Hu; Xu Zou; Ruiping Han; Mingtao Quan (BMJ Open)
Introduction Oropharyngeal colostrum administration (OCA) confers immunological benefits to very low birth weight infants (VLBWIs) through nutrient absorption via oropharyngeal lymphatic tissue, potentially reducing complication rates and improving clinical outcomes. Current evidence demonstrates significant variability in OCA protocols regarding the initiation timing, application frequency, treatment duration and dosage of this therapy across studies, and limited research exists on its impact on haematological indices in infants. Notably, the dose-dependent effects of OCA on both clinical outcomes and haematological immunological parameters in VLBWIs remain insufficiently investigated. We hypothesise that varying OCA doses will demonstrate differential impacts on clinical outcomes and systemic levels of key immunological markers in VLBWIs.Methods and analysis This single-centre, three-arm, parallel-controlled randomised controlled trial will enrol 129 VLBWIs to evaluate the efficacy of OCA. Using a blinded design, both outcome assessors and data analysts will be masked to group allocation throughout the study. Participants will be randomly assigned in a 1:1:1 ratio into three groups: two receiving OCA (0.2 mL colostrum every 3 hours or 6 hours for 10 days) and a control group with standard care only. The primary endpoints of this trial are to compare the incidence of necrotising enterocolitis, bronchopulmonary dysplasia and retinopathy of prematurity across the three groups. Additionally, we will assess haematological and immunological indicators, including IL-2, IL-4, IL-6, IL-10, TNF-α, IFN-γ and serotype immunoglobulin A levels, to evaluate the potential effects of different OCA dosages on these parameters.Ethics and dissemination This study protocol received full ethical approval (No. KLL-2023–505) from the ethics committee of the Affiliated Hospital of Zunyi Medical University on 5 September 2023, after a thorough review. The study findings will be disseminated through publication in peer-reviewed journals.Trial registration number ChiCTR2300077114. Registration on 31 October 2023.